Vocational and Technical Education Lecturers’ Preparedness in Adopting The Emerging Technology Posed By Covid-19 Pandemic - Adeolu Oludare Olatoye; SARAFADEEN SEGUN SALAMI; Rasidat Iyabo Olore; Adeola Idiat Adepoju (Journal of Digital Learning and Education, 2022)
The study was carried out to examine the preparedness of vocational and technical education lecturers in adopting the emerging technology posed by Covid-19 pandemic in Oyo State Colleges of Education, Nigeria.  To achieve the objectives of the study, two research questions were developed and answered while one null hypothesis was tested at 0.05 level of significance.  The study adopted survey research design.  The population for the study consisted of 150 lecturers.  Total enumeration sampling technique was used for this research work.  The questionnaire was faced and content validated by two experts from the Department of Business Education and one expert from Industrial Technical Education Department, Tai Solarin University of Education, Ijebu-ode.  Cronbach Alpha method was adopted to ensure reliability of the instrument with the coefficient of r=0.96.  This shows that the instrument is highly reliable.  The questionnaire was administered on 150 respondents and all were successfully retrieved.  Mean and Standard deviation were used to answer data related to research questions while t-test analysis was used to test the null hypotheses at 0.05 level of significance.  The findings of the study revealed that preparedness level of the Vocational and Technical Education lecturers on the use of available technological tools for teaching and learning is moderately high.  Based on the findings, it was recommended among others that government through a relevant agency like Tertiary Education Trust Fund (TETFund) should assist in providing some adequate modern technological tools for Colleges of Education, school management should provide modern technological tools for the smooth running of teaching and learning, Seminars and Conferences on the use of modern technological tools be attended at an interval.